2015
DOI: 10.1186/s12889-015-2449-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a measure of health-related production loss: construct validity and responsiveness - a cohort study

Abstract: BackgroundThe aim of this study is to evaluate the construct validity and responsiveness of a Swedish measure of health-related production loss as well as to investigate if there is a difference in the level of production loss within a population suffering from persistent back/neck pain and CMDs.MethodsThe sample was drawn from a study that assessed employees’ health and working capacity in 74 health care units before and after intervention. The study included 692 patients who reported working the previous six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The WPAI-GH is composed of six items assessing deficits in work productivity and activities in the past seven days. This questionnaire is scored on the basis of four indicators: the percentage of time lost from work due to health conditions (absenteeism), the percent reduction in work effectiveness due to health conditions (presenteeism), the percentage of overall work productivity lost due to health conditions (absenteeism and presenteeism), and the percent decline in activities of daily living (ADL) outside of work due to health conditions, with higher scores indicating longer absence due to sickness or lower productivity 10 .…”
Section: Methodsmentioning
confidence: 99%
“…The WPAI-GH is composed of six items assessing deficits in work productivity and activities in the past seven days. This questionnaire is scored on the basis of four indicators: the percentage of time lost from work due to health conditions (absenteeism), the percent reduction in work effectiveness due to health conditions (presenteeism), the percentage of overall work productivity lost due to health conditions (absenteeism and presenteeism), and the percent decline in activities of daily living (ADL) outside of work due to health conditions, with higher scores indicating longer absence due to sickness or lower productivity 10 .…”
Section: Methodsmentioning
confidence: 99%
“…The domain of bodily pain, especially, showed a negative and significant correlation with all domains of productivity loss. Previous studies of various instruments to measure productivity loss have shown that the quality of life correlates negatively with productivity loss [ 27 , 28 , 29 ]. The results of our study are consistent with those of these reports.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that each domain of productivity loss (absenteeism, presenteeism, and unpaid work) estimated by the iPCQ was negatively correlated with the quality of life. In general, it is known that a patient’s health problem has an effect on the measurement of the health-related productivity loss [ 25 , 26 , 27 , 28 , 29 ]. We classified the correlations into the follow categories: high correlation (r ≥ |0.3|) and low correlation (r < |0.3|) [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Presenteeism (reduced performance while being present at work) and absenteeism (hours and days missed from work due to sickness absence) will be measured by questionnaire every 4 weeks [ 44 , 45 ]. In addition, sickness absence data (absenteeism) will be retrospectively collected from company records after the last follow-up measurement.…”
Section: Methodsmentioning
confidence: 99%